2017
DOI: 10.3389/fcimb.2017.00453
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Shock Domain Family Proteins (Csps) Are Involved in Regulation of Virulence, Cellular Aggregation, and Flagella-Based Motility in Listeria monocytogenes

Abstract: Cold shock-domain family proteins (Csps) are highly conserved nucleic acid binding proteins regulating the expression of various genes including those involved in stress resistance and virulence in bacteria. We show here that Csps are involved in virulence, cell aggregation and flagella-based extracellular motility of Listeria monocytogenes. A L. monocytogenes mutant deleted in all three csp genes (ΔcspABD) is attenuated with respect to human macrophage infection as well as virulence in a zebrafish infection m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(97 citation statements)
references
References 57 publications
3
92
0
2
Order By: Relevance
“…Bacterial Csps are highly conserved small multifunctional nucleic acid‐binding proteins that mediate a wide range of physiological functions, including stress resistance and virulence‐associated responses, by modulating transcription, translation and mRNA stability (Eshwar et al ., ; Schärer et al ., ). Csps have been identified as major determinants of pathogenicity in various disease‐causing bacteria, including Enterococcus faecalis , Staphylococcus aureus , Salmonella enterica , Brucella melitensis and Listeria monocytogenes (Eshwar et al ., ; Michaux et al ., , ; Sahukhal and Elasri, ; Wang et al ., ). Despite extensive research during the last decade, the molecular mechanism underlying the association of Csps and virulence has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial Csps are highly conserved small multifunctional nucleic acid‐binding proteins that mediate a wide range of physiological functions, including stress resistance and virulence‐associated responses, by modulating transcription, translation and mRNA stability (Eshwar et al ., ; Schärer et al ., ). Csps have been identified as major determinants of pathogenicity in various disease‐causing bacteria, including Enterococcus faecalis , Staphylococcus aureus , Salmonella enterica , Brucella melitensis and Listeria monocytogenes (Eshwar et al ., ; Michaux et al ., , ; Sahukhal and Elasri, ; Wang et al ., ). Despite extensive research during the last decade, the molecular mechanism underlying the association of Csps and virulence has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…() and Eshwar et al . () reported that Csps regulate the production of the pore‐forming cytolysin listeriolysin, haemolysis phenotypes, cell aggregation and flagella‐based motility in Listeria monocytogenes . Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, tdh from the clinical strain VP1 that was cultured in shrimp samples demonstrated a lower expression level at 9 • C, indicating that the gene expression at a low temperature was irregular among different strains and matrices [48]. Bacterial Csps are vastly conserved small multifunctional nucleic acid-binding proteins that mediate a wide range of physiological functions, including regulation of growth under both normal and cold conditions, stress resistance, and virulence-associated responses, by modulating transcription, translation, and mRNA stability [49]. Csps have been identified as major determinants of pathogenicity in several foodborne disease-causing bacteria, such as Listeria monocytogenes [49], Staphylococcus aureus [50], and Brucella melitensis [51].…”
Section: Effect Of Cold Shock On Gene Expression Of Nonpathogenic (Vpmentioning
confidence: 99%
“…Bacterial Csps are vastly conserved small multifunctional nucleic acid-binding proteins that mediate a wide range of physiological functions, including regulation of growth under both normal and cold conditions, stress resistance, and virulence-associated responses, by modulating transcription, translation, and mRNA stability [49]. Csps have been identified as major determinants of pathogenicity in several foodborne disease-causing bacteria, such as Listeria monocytogenes [49], Staphylococcus aureus [50], and Brucella melitensis [51]. Our study showed the V. parahemolyticus growth upon cold shock and the induction of cspA gene, which suggest, respectively, cellular adaptive mechanisms and an altered metabolic recovery.…”
Section: Effect Of Cold Shock On Gene Expression Of Nonpathogenic (Vpmentioning
confidence: 99%
“…Since mutagenesis experiments in E. coli , Yersinia enterocolitica and Salmonella show that one or more CSPs can be functionally compensated by the remaining non‐mutated homologs, it is thought that CSPs might have redundant roles. However, not all CSPs can totally restore the function of their mutated paralogs, suggesting a certain degree of specificity among them (Eshwar, Guldimann, Oevermann, & Tasara, ; Michaux et al, ; Neuhaus, Rapposch, Francis, & Scherer, ; Xia, Ke, & Inouye, ).…”
Section: Introductionmentioning
confidence: 99%